Bentuk Peranan Guru Dalam Memberikan Pendidikan Kepemimpinan - Sophia Azhar (el-Idarah: Jurnal Manajemen Pendidikan Islam, 2019)
Indonesia, as many experts mention, has interminable problems of leadership. As a country in which Muslims are the majority, everyone should realize that all are born as a leader who shall have the responsibility upon people’s welfare. But in reality, Indonesians are not wellbeing physically or spiritually. It absolutely defines that a leader should possess leadership knowledge to lead people, not only depend on the God’s will solely. A leader is not an innate. For this purpose, teachers have the responsibility and important role to succeed the educational leadership as earlier as possible. This article is a descriptive discussion which is aimed at describing the roles of teacher as motivator, leader, problem solver and students’ ally in modeling the leadership. The discussion shows that all the four roles of teachers give positive effect in gaining the learning objectives of educational leadership.